Lipase Assisted (S)-Ketoprofen Resolution from Commercially Available Racemic Mixture - Daniela Estrada-Valenzuela; Víctor H. Ramos-Sánchez; Gerardo Zaragoza-Galán; Jose C. Espinoza-Hicks; Alejandro Bugarin; David Chávez-Flores (MDPI AG, 2021)
Ketoprofen is a commercially available drug sold as a racemic mixture that belongs to the family of non-steroidal anti-inflammatory drugs known as profens. It has been demonstrated (in vitro) that (S)-ketoprofen is around 160 times more potent than its enantiomer (R)-ketoprofen, while accumulation of (R)-ketoprofen can cause serious side effects, such as dyspepsia, gastrointestinal ulceration/bleeding, pain, salt and fluid retention, and hypertension. In this work, four commercially available lipases were systematically assessed. Parameters such as conversion, enantiomeric excess, and enantioselectivity were considered. Among them, and by evaluating lipase load, temperature, solvent, and alcohol, Candida rugosa lipase exhibited the best results in terms of enantioselectivity E = 185 ((S)-enantiopreference) with esterification conversions of c = 47% (out of 50%) and enantiomeric excess of 99%. The unreacted (R)-enantiomer was recovered by liquid-liquid extraction and racemized under basic media, which was recycled as starting material. Finally, the (S)-alkyl ketoprofen ester was successfully enzymatically hydrolyzed to the desired (S)-ketoprofen with c = 98.5% and 99% ee. This work demonstrated the benefit and efficiency of using Candida rugosa lipase to kinetically resolve racemic ketoprofen by an environmentally friendly protocol and with the recycling of the undesired (R)-ketoprofen.